Dose and time response of ruminally infused algae on rumen fermentation characteristics, biohydrogenation and Butyrivibrio group bacteria in goats. Issue 1 (December 2016) - Zhu, Honglong; Fievez, Veerle; Mao, Shengyong; He, Wenbo; Zhu, Weiyun
Abstract Background Micro-algae could inhibit the complete rumen BH of dietary 18-carbon unsaturated fatty acid (UFAs). This study aimed to examine dose and time responses of algae supplementation on rumen fermentation, biohydrogenation andButyrivibrio group bacteria in goats. Methods Six goats were used in a repeated 3 × 3 Latin square design, and offered a fixed diet. Algae were infused through rumen cannule with 0 (Control), 6.1 (L-Alg), or 18.3 g (H-Alg) per day. Rumen contents were sampled on d 0, 3, 7, 14 and 20. Results H-Alg reduced total volatile fatty acid concentration and acetate molar proportion (P  < 0.05), and increased propionate molar proportion (P  < 0.05), whereas L-Alg had no effect on rumen fermentation. Changes in proportions of acetate and propionate in H-Alg were obvious from d 7 onwards and reached the largest differences with the control on d 14. Algae induced a dose-dependent decrease in 18:0 and increasedtrans -18:1 in the ruminal content (P  < 0.05). H-Alg increased the concentrations oft 9, t 11-18:2 andt 11, c 15-18:2 (P  < 0.05). L-Alg only seemed to induce a transient change in 18-carbon isomers, while H-Alg induced a rapid elevation, already obvious on d 3, concentrations of these fatty acid rose in some cases again on d 20. Algae had no effect on the abundances ofButyrivibrio spp. andButyrivibrio proteoclasticus (P  > 0.10), while H-Alg reduced the total bacteria abundance (P  < 0.05). However, this was induced by a significant difference between control and H-Alg on d 14 (-4.43 %). Afterwards, both treatments did not differ as increased variation in the H-Alg repetitions, with in some cases a return of the bacterial abundance to the basal level (d 0). Conclusions Changes in rumen fermentation and 18-carbon UFAs metabolism in response to algae were related to the supplementation level, but there was no evidence of shift in ruminal biohydrogenation pathways towardst 10-18:1. L-Alg mainly induced a transient effect on rumen biohydrogenation of 18-carbon UFAs, while H-Alg showed an acute inhibition and these effects were not associated with the known hydrogenating bacteria.